Menguak Status dan Legalitas Rupiah Digital sebagai Legal Tender (Perspektif Teori Keadilan Bermartabat) - Setjoatmadja, Sylvia; Kameo, Jeferson (UI Scholars Hub, 2025)
Digital technology and modern telecommunications have been and will continue to be key factors in the emergence of various innovative products. One such innovative product is digital currency, specifically Central Bank Digital Currency (CBDC). In Indonesia, advancements in digital technology and telecommunications have encouraged the government to issue a CBDC, which will be named Digital Rupiah. The initiative to issue Digital Rupiah also responds to global trends and the public's need for secure, efficient, and sustainable payment instruments. However, the plan to issue Digital Rupiah is not without challenges, particularly regarding the clarity of its legal status as a lawful means of payment or legal tender. Using a normative legal research method, this study finds that Article 23B of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) does not explicitly regulate the types of digital currency. There exists a *rechtsvacuum* (legal void) concerning the legal tender status of Digital Rupiah at the constitutional level. Additionally, from a technical-juridical perspective, concrete legal regulations regarding the status and legal tender legality of Digital Rupiah, in parity with paper and coin Rupiah, remain insufficiently comprehensive. Such legal conditions have the potential to create ambiguity and uncertainty. Nevertheless, this study identifies the emergence of a new law in the form of an omnibus law, which serves as a supporting framework for the solidity of the legal structure as well as a source of clarity on the meaning, status, and legality of Digital Rupiah. The clarity of such a legal framework is essential to solidify the innovation in the issuance and use of Digital Rupiah in the digital era. The legal framework for Digital Rupiah will support payment system efficiency, promote financial inclusion, and contribute to sustainable national economic growth. The legal theory guiding the research findings, which emphasizes the comprehensive regulation of CBDC, is the Dignified Justice Theory. According to this theory, while the need for legal comparison is unavoidable, Pancasila must remain the ultimate source of all legal principles governing the existence of Digital Rupiah.